Inhibition of [methyl-3H]diazepam binding to rat brain membranes in vitro by dinatin and skrofulein - Shen Xing-liang; Nielsen Mogens; Witt Michael Robin; Sterner Olov; Bergendorff Ola; Khayyal Mohamed (Acta Pharmacologica Sinica, 2016)
Two flavones, 4',5,7-trihydroxy-6-methoxy flavone (dinatin) and 4',5-dihydroxy-6, 7-dimethoxy flavone (skrofulein), were extracted from Artemisia herba alba L. Dinatin and skrofulein inhibited the binding of [methyl-3H]diazepam to rat brain membranes in vitro with IC50 of 1.3 and 23 mumol.L-1, respectively. The GABA-ratios (the ratio of IC50 values in the absence/presence of GABA in the binding assay) were 1.1 and 1.2 for dinatin and skrofulein, respectively. Both flavones induced a slight increase in [35S] TBPS binding. The data suggest that the flavones are antagonists or partial agonists of benzodiazepine receptors.